(3UfGOjb GdESJKeGQ Hjf GdEbJUGO GdESdGej hGdEbJUGO GdhVYjs - (3fRjg YHO GdebUhO(B, (3eHQhcs ((3GdGScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2006)
(3jVe GSJKeGQ GdeGd aj GdGbJUGO GdGSdGej, eGgjI UfGOjb GdGSJKeGQ, GdJcjja GdbGfhfj hGdVQjHj hGdTQYj dUfGOjb GdGSJKeGQs
(3HHdjhZQGajG(B: (3U(B.162-179s
Keywords: (3GdGSJKeGQs; (3GdGbJUGO GdGSdGejs